Advances in genomics for diversity studies and trait improvement in temperate fruit and nut crops under changing climatic scenarios - Manzoor, Ikra; Samantara, Kajal; Bhat, Momin Showkat; Farooq, Iqra; Bhat, Khalid Mushtaq; Mir, Mohammad Amin; Wani, Shabir Hussain (Frontiers in Plant Science, 2023)
Genetic improvement of temperate fruit and nut crops through conventional breeding methods is not sufficient alone due to its extremely time-consuming, cost intensive as well as hard to handle approach. A few other constraints that are associated with these species viz., their long juvenile period, high heterozygosity, sterility, presence of sexual incompatibility and polyploidy etc., makes their selection and improvement process more complicated. Therefore, to promote precise and accurate selection of plants based on their genotypes, supplement of advance biotechnological tools viz., molecular marker approaches along with traditional breeding methods is highly required in these species. Different markers especially the molecular ones enable direct selection of genomic regions governing the trait of interest such as high quality, yield, resistance to abiotic and biotic stresses, etc., instead of the trait itself thus, saves the overall time and space, help screening fruit quality and other related desired traits at early stages. The availability of molecular markers like SNP (Single Nucleotide Polymorphism), DArT (Diversity Array Technology) markers, and dense molecular genetic maps in crop plants, including fruit and nut crops led to reveal facts from genetic markers thus, assist in precise line selection. This review highlighted several aspects of molecular marker approach that opens up tremendous possibilities to reveal valuable information about genetic diversity and phylogeny to boost the efficacy of selection in temperate fruit crops through genome sequencing and thus, cultivar improvement with respect to adaptability and biotic and abiotic stress resistance in temperate fruit and nut species.